Pelatihan Charting dengan Microsoft Excel Sebagai Sarana Pembelajaran Matematika di SMP Kristen Kefamenanu - Justin Eduardo Simarmata; Ferdinandus Mone; Yosepha Patricia Wua Laja; Hendrika Bete; Maria Naimnule; Juventianus Kenjam; Debora Chrisinta (UNIB Press, 2023)
Mathematics learning carried out at SMP Kristen Kefamenanu refers to a teacher-centered learning system. Microsoft Excel is one application that can be used as a medium for learning mathematics to make it easier for students to solve problems, especially those related to the presentation of graphs. SMP Kristen Kefamenanu has a Computer Laboratory which also has a Microsoft Excel application. The purpose of this service is to provide Charting training using Microsoft Excel as a means of mathematics learning tool to students in SMP Kristen Kefamenanu. The activity was carried out for two days, and during the course of the activity students showed enthusiasm and were able to follow directions during the activity. The results of feedback given by students on the answers to the satisfaction questionnaire showed that students gave categories of strongly agree and agree on 18 questions. This shows that the existence of PKM activities that have been carried out can help students better understand mathematics lessons delivered at school, as well as increase knowledge for students in using Microsoft Excel as a tool for mathematics learning.